(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
VULNERABILITY AND DEMOCRACY IN IBERO-AMERICA Authors: Federico Aznar and Marisa Ramos. Publisher: Tirant lo Blanch, Monografías collection, 2015, 372 pages. ISBN: 978-8490867792